PENGARUH KEPEMILIKAN MANAJERIAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (Struktur Modal sebagai Variabel Moderasi) - Suastini, Ni Made; Purbawangsa, Ida Bagus Anom; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The Company has a long-term goal to maximize shareholder wealth. This objective is achieved by increasing the company's value will be reflected in its stock price. This study aims to determine the effect of managerial ownership and growth of the company to corporate value, using the capital structure as a moderating variable. The study sample as many as 19 companies conducted in manufacturing companies listed on the Indonesia Stock Exchange. Observation period 2010 to 2013. The research hypothesis testing using analysis techniques moderated regression analysis (MRA). The results showed that: (1) managerial ownership negative effect significantly to the value of the company (2) the growth of the company significant positive effect on the value of the company (3) the capital structure positive effect was not significant to the value of the company (4) The capital structure was not able to moderate the influence of managerial ownership the value of the company (5) capital structure was not able to moderate the effect of growth on firm value.
Keywords: Managerial Ownership, Company Growth, Capital Structure, and Firm Value